(untitled) (Issues in Social and Environmental Accounting (ISEA), 2015)
Due to environment protection issue, waste management becomes one of important factors in maintaining organization sustainability. In developed country, a growing number of companies began to integrate the pro environment practices, such as waste management practices, into their business strategy. In contrast, the implementation of waste management practices by business organizations in developing country, like Indonesia, is still rare. Waste generated by industries is greater than the capacity to manage this volume of waste. This poses a problem that leads to improper disposal of waste and pollution. This study aims to design a research model which investigates the relation of institutional environment including cognitive, regula tory, and normative element; manager environmental attitudes, worker environmental attitudes, environmental policy, strategic waste management practices, and financial performance.